War, Will, and Warlords Counterinsurgency in Afghanistan and Pakistan, 2001-2011 - Cassidy, Robert M. (Marine Corps University Press (MCUP), 2012)
This book lies at the intersection of international security studies, military strategy, and the operational art of counterinsurgency. For conventional militaries to be successful in counterinsurgency and irregular warfare, they must adapt their means and methods to meet the exigencies of a range of lethal and nonlethal actions and activities. In addition, the methods of Coalition partners should generally be collaborative, designed to adequately implement the principles and tenets of counterinsurgency in complementary ways. This book identifies best and worst practices in both counterinsurgency and counterterrorism operations in Pakistan and Afghanistan with the aim of crafting recommendations for more effective counterinsurgency.